Look : how to pay attention in a distracted world - Madsbjerg, Christian (Riverhead Books, 2023)
"A fascinating exploration of how we pay attention that will transform the ways we connect with each other--at work, at home, and beyond. We've forgotten how to pay attention, Christian Madsbjerg says in his provocative new book. Listening carefully and observing intentionally are crucial human skills, yet we're not born knowing how to do them. And thanks to the ubiquity of social media, increasing social isolation, and the use of empty imagery and ideology as stand-ins for direct observation, we're losing our ability to interpret the world at a time when we desperately need to do that. Madsbjerg, a consultant and a professor at the New School, noticed this disturbing trend and in 2015 began to coteach a course on human observation called Human Observation. To his surprise, the course has been oversubscribed since the beginning, with hundreds of students--philosophy and business majors, undergrads and graduate students--signing up for it, and hundreds more on waiting lists. In this book, Madsbjerg argues that most of us are stuck in bad habits of looking at the world without truly seeing it, and he guides us through the key observational skills we need to explain how we can recapture our ability to truly pay attention--what he calls "the meta-skill of observation." Pulling from his own background and drawing examples from the arts, philosophy, and beyond, Madsbjerg has written a book of insight and practical wisdom that highlights how we can pay sharper attention to live with more empathy and connect better with others"--